1993
DOI: 10.1016/0014-5793(93)81724-e
|View full text |Cite
|
Sign up to set email alerts
|

Role of a serum phospholipase A1in the phosphatidylserine‐induced T cell inhibition

Abstract: We have previously shown that unsaturated phosphatidylserines inhibit mitogen‐induced T cell activation. We now report that the inhibitory action requires a protein present in bovine and human serum. Partial purification and phospholipase assay show that this protein has phospholipase A activity on phosphatidylserine but not phosphatidylethanolamine, phosphatidylcholine and phosphatidylinositol. In short incubations (1–3 h) 2‐acyl lysophosphatidylserine is produced but in longer incubations the cis‐unsaturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…After 24 hours, the total RNA of the cells was purified using the GenElute mammalian total RNA Miniprep kit (Sigma-Aldrich Co.) and LysoPS is thought to act as a potent lipid mediator, similar to LysoPA and S1P 9) . For example, LysoPS stimulates the degranulation of mast cells 10,11) , suppresses the proliferation of T lymphocytes 12) and induces apoptotic cell engulfment by macrophages 13,14) .…”
Section: Analysis Of the Gene Expression Using Real-time Rt-pcrmentioning
confidence: 99%
“…After 24 hours, the total RNA of the cells was purified using the GenElute mammalian total RNA Miniprep kit (Sigma-Aldrich Co.) and LysoPS is thought to act as a potent lipid mediator, similar to LysoPA and S1P 9) . For example, LysoPS stimulates the degranulation of mast cells 10,11) , suppresses the proliferation of T lymphocytes 12) and induces apoptotic cell engulfment by macrophages 13,14) .…”
Section: Analysis Of the Gene Expression Using Real-time Rt-pcrmentioning
confidence: 99%
“…We have purified and cloned a cDNA for phosphatidylserine-specific PLA 1 (PS-PLA 1 ), a member of the lipase family, from the culture medium of activated rat platelets. PS-PLA 1 specifically hydrolyzes PS (24) and produces 2-acyl-lysophosphatidylserine (LPS), which is a lipid mediator for mast cells (25), T cells (26), and neural cells (27). We recently showed that PS-PLA 1 stimulates histamine release from rat peritoneal mast cells by hydrolyzing PS exposed on the surface of some cell types such as apoptotic cells and activated platelets (25).…”
mentioning
confidence: 99%
“…For example, lyso-PS is demonstrated to interact with local mast cells (17), producing specific and stereoselective activation (18). It also induces transient increases in cytosolic free Ca 2ϩ ([Ca 2ϩ ] i ) in ovarian and breast cancer cells (19) and lyso-PS; 2-acyl-1-lyso-PS with unsaturated fatty acids especially inhibits mitogen-induced T cell activation (20). Lyso-PS is present in human serum, the aqueous humor and the lachrymal gland fluid of the eye (21).…”
mentioning
confidence: 99%